2015
DOI: 10.17219/acem/38144
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Resveratrol Against Glutamate-Induced Excitotoxicity

Abstract: As the major neurotransmitter in the mammalian central nervous system (CNS), excessive extracellular glutamate (Glu) can activate the Glu receptors and neuronal calcium (Ca2+) overload, then produce neurotoxicity, which is a common pathway for neuronal injury or death, and is associated with acute and chronic neurodegenerative diseases. Therefore, it has been a therapeutic strategy to investigate neuroprotective effects against Glu-induced neurotoxicity for treating both acute and chronic forms of neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
0
16
0
4
Order By: Relevance
“…The present study found that resveratrol reduced the number of alcohol-induced microglial cells and neuron cells, and inhibited the increased levels of NF-κB, TNF-α, SOD and GSH in alcohol-induced rats. Zhang et al reported the neuroprotective effects of resveratrol against glutamate-induced excitotoxicity in neurodegenerative diseases (14), and Abengózar-Vela et al demonstrated that resveratrol reduced inflammatory and oxidative damage in human ocular surface epithelial cells (15). AMPK has protective and reparative effects on developing and mature neurons, which can enhance the uptake of neurons cultured in vitro and promote the differentiation of neurons (16).…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that resveratrol reduced the number of alcohol-induced microglial cells and neuron cells, and inhibited the increased levels of NF-κB, TNF-α, SOD and GSH in alcohol-induced rats. Zhang et al reported the neuroprotective effects of resveratrol against glutamate-induced excitotoxicity in neurodegenerative diseases (14), and Abengózar-Vela et al demonstrated that resveratrol reduced inflammatory and oxidative damage in human ocular surface epithelial cells (15). AMPK has protective and reparative effects on developing and mature neurons, which can enhance the uptake of neurons cultured in vitro and promote the differentiation of neurons (16).…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs are being investigated along with natural products such as resveratrol. This naturally occurring polyphenol, mainly found in grapes and red wine, has shown in vitro and in vivo neuroprotective effects for a variety of experimental models of neurodegenerative diseases (Zhang et al, 2015). This and other natural products such as TUDCA (Fernandez-Sanchez et al, 2011) or safranal deserve further investigation .…”
Section: A Look Into the Futurementioning
confidence: 99%
“…Resveratrol is also able to enhance hippocampal plasticity and hippocampal neurogenesis [ 17 ]. Recently, a number of studies have focused on the neuroprotective effects of resveratrol, including its ability to diminish the toxicity induced by the amyloid beta peptide [ 18 , 19 ] and kainic acid [ 20 ], as well as prevent cerebral ischemic damage [ 16 , 21 ]. In addition, animal studies have demonstrated the efficacy of resveratrol to reverse learning and memory impairments in aged animals [ 16 , 22 ].…”
Section: Introductionmentioning
confidence: 99%